Continuing Health Education in elderly care: difficulties and facilitators of the Family Health Support Center - Iara Sescon Nogueira; Vanessa Denardi Antoniassi Baldissera (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objectives: To analyze the difficulties and facilitators of Continuing Health Education developed by the Núcleos de Apoio à Saúde da Família (NASF - Family Health Support Centers) in elderly care. Method: A qualitative and exploratory-descriptive study was developed with 46 NASF professionals. Data were obtained with the Focus Group technique and analyzed with basic lexicography using the IRaMuTeQ® software, through Word Clouds. The theoretical-analytical framework adopted was Freire's Dialogical Theory. Results: The difficulties of Continuing Health Education in elderly care were experienced more frequently than facilitators, which were associated with lack of support, instruments and resources. Conclusion and implications for practice: Portraying Continuing Health Education can contribute to the reflection, planning and evaluation of educational practices and elderly care practiced by the NASF.